Norming the female body: discourses of sexuality in Dante Gabriel Rossetti, Christina Rossetti and Algernon Charles Swinburne - Acón-Chan, Lai Sai (Universidad de Costa Rica. Campus Rodrigo Facio. Sitio web: https://www.ucr.ac.cr/ Teléfono: (506) 2511-4000. Correo de soporte: revistas@ucr.ac.cr, 2014)
This article explores the contradictions resulting from sexual discourse constructed in the nineteenth century from a hegemonic model that determines sexual rigid sex roles of Victorian English society. Some literary works of Dante Gabriel Rossetti, Christina Rossetti and Charles Swinburne related with these issues are discussed.